THE EFFECT OF ASSET-LIABILITY MANAGEMENT ON SHARIA BANK PERFORMANCE - Nazifah, Nauroh; Sukardi, Budi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2023)
The purpose of this study was to determine the health level of Bank Muamalat Indonesia (BMI) and Bank Syariah Indonesia (BSI) and to determine the difference in the health level of Bank Muamalat and Bank Syariah Indonesia. The population in this study were BSI and BMI, the sample used BSI and BMI quarterly financial report data from 2015-2022. The analysis technique uses multiple linear regression analysis and independent sample t-test. At BMI, the CR and CAR ratios have no effect on ROA, only the BOPO ratio has an effect on ROA. Then at BSI, the CR and BOPO ratios affect ROA, while the CAR ratio has no effect on ROA. The results of the independent t-test show that there are differences between BMI and BSI on ROA, CR, CAR, and BOPO. The conclusion shows that both in BMI and BSI the CR variable affects ROA and there are differences in performance between BMI and BSI banks where the performance of Bank Syariah Indonesia is better than Bank Muamalat.